Picky Eating Habits and Stunting Among Preschool Children in Nogotirto Village, Sleman Regency, Special Region of Yogyakarta, Indonesia - Annisa, Nada Nur; Hasanah, Laeli Nur (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Nutritional problems among preschool children, particularly stunting, remain a major public health concern in Indonesia. One eating behavior that may influence nutritional status is picky eating. This study aimed to analyze the relationship between picky eating habits and nutritional status based on the height-for-age index (HFA) among preschool children in Nogotirto Village, Gamping District, Sleman Regency, Special Region of Yogyakarta, Indonesia. This quantitative study employed a cross-sectional design involving 95 children aged 24–59 months selected through purposive sampling. Data were collected using a demographic questionnaire and the Child Eating Behaviour Questionnaire (CEBQ), while nutritional status was assessed using the height-for-age index (HFA) based on direct height measurements obtained with a stadiometer. Data were analyzed using Spearman’s correlation test. The results showed that 41.1% of the children exhibited picky eating behavior, and a significant association was found between picky eating habits and nutritional status based on height-for-age (p=0.032; r=0.220). Lower levels of picky eating were generally associated with better nutritional status. These findings highlight the importance of early interventions aimed at improving children's eating behaviors to support optimal growth and reduce the risk of stunting.